Perencanaan Jaringan 5G Menggunakan Teknologi Macrocell dan Picocell - Rivan Achmad Nugroho; Redy Ratiandi Yacoub; Herry Sujaini; Dedy Suryadi; Eva Faja Ripanti (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2025)
The city of Pontianak is projected to experience substantial growth in network demand, driven by the expansion of commercial hubs, educational institutions, tourism destinations, and essential public services. Under the current status quo, Pontianak lacks 5G network coverage, underscoring the necessity of implementing a comprehensive 5G network plan to support its urban development. This research conducted a detailed analysis of 5G network coverage and capacity planning, utilizing macrocell and picocell technologies to address the connectivity demands of an urban environment. Operating within the 3.5 GHz frequency band with a 100 MHz bandwidth, this research examined network requirements in the medium band spectrum. The results revealed that macrocell technology required 18 uplink and 23 downlink sites to cover an area of 107.8 km², while picocell technology demanded a denser infrastructure, comprising 351 uplink and 364 downlink sites across 90.72 km². Based on a five-year capacity projection for a population of 673,400, the macrocell technology will require 10 uplink and 22 downlink sites. On the contrary, picocell technology, which is more suitable for densely populated areas, will require 261 uplink and 263 downlink sites to serve a population of 423,881. Simulation results indicated that synchronization signal reference signal received power (SS-RSRP) and secondary synchronization signal received power (SS-SINR) values met or surpassed the established key performance indicators (KPI) for both technologies. This 5G network plan aligns with Pontianak’s smart city vision by enhancing connectivity, optimizing coverage, and delivering seamless user experiences, highlighting the adaptability of macrocell and picocell solutions in varied urban settings.